2014
DOI: 10.1634/theoncologist.2014-0180
|View full text |Cite
|
Sign up to set email alerts
|

How to Implement a Geriatric Assessment in Your Clinical Practice

Abstract: Cancer is a disease that mostly affects older adults. Other health conditions, changes in functional status, and use of multiple medications change the risks and benefits of cancer treatment for older adults. Several international organizations, such as the International Society of Geriatric Oncology, the European Organization for Research and Treatment of Cancer, recommend the conduct of a geriatric assessment (GA) for older adults with cancer to help select the most appropriate treatment and identify any und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 158 publications
0
41
0
1
Order By: Relevance
“…The median time to complete the eRFA for preoperative assessment was an acceptable 11 minutes, which is similar to the time it takes to complete a screening assessment (rather than a complete GA) 18 and is much shorter than the time reported to complete a paper-version GA (30 minutes). 19 In addition, the majority of patients were able to complete the eRFA on their own or with assistance from a caregiver.…”
Section: Discussionmentioning
confidence: 76%
“…The median time to complete the eRFA for preoperative assessment was an acceptable 11 minutes, which is similar to the time it takes to complete a screening assessment (rather than a complete GA) 18 and is much shorter than the time reported to complete a paper-version GA (30 minutes). 19 In addition, the majority of patients were able to complete the eRFA on their own or with assistance from a caregiver.…”
Section: Discussionmentioning
confidence: 76%
“…13 To contend with this problem, brief screening instruments and geriatric assessments to detect major geriatric-associated problems are used more and more to formally evaluate older patients with cancer, 14 and there is a call to perform at least a screening before treatment initiation. An extensive body of data has shown that geriatric assessment can identify major issues not usually found by oncologists, many with proven beneficial interventions (eg, falls).…”
Section: Geriatric Assessment and Estimating Life Expectancymentioning
confidence: 99%
“…15 The use of performance status as a global estimation of function for older patients is inadequate. 14 An estimation of life expectancy should be done for all older patients before making a treatment plan. 16 We prefer the Cancer and Aging Research Group (www.mycarg.org) tool 17 for performing a brief geriatric assessment because its use is feasible in the clinical trial and community settings 18 and because it can be used to predict chemotherapy-related toxicity.…”
Section: Geriatric Assessment and Estimating Life Expectancymentioning
confidence: 99%
“…Though moderate and advanced dementia patients are less often evaluated by oncologists, patients with incipient deficits are not infrequent in daily practice [33]. Different studies based on epidemiological databases show large differences in treatment patterns between cognitively impaired (or dementia) and non-cognitively impaired patients, with the former receiving all treatment modalities less often [34,35].…”
Section: Cognitive Impairment and Social Issuesmentioning
confidence: 99%
“…No specific instruments exists for adjuvant chemotherapy but it is reasonable to use any of the tools evaluated on the international society of geriatric oncology (SIOG) consensus and in the systematic review by Puts et al [54] [62]. CGA evaluates the following core domains: functional status, cognition/depression, comorbidity (a prognostic factor for elderly women with breast cancer [63]), falls, social support, nutrition and polypharmacy [33]. It is important to note that classic oncologic tools such as ECOG performance status and Karnovsky score are not a part of CGA and underperform in the elderly [60,64].…”
Section: Comprehensive Geriatric Assessmentmentioning
confidence: 99%